The Impact of Modern Topo-Geodetic Technologies on Positioning Techniques - Mircea Emil NAP; Petre Iuliu DRAGOMIR; Silvia CHIOREAN; Jutka DEAK; Ioan LUPUȚ; Diana FICIOR (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2021)
The field of constructions has evolved extraordinarily in terms of measurement techniques, requiring increasing accuracy. This has led to the creation of new specific technologies, and implicitly measuring instruments. The range of classical geodetic measuring instruments has been completed with new high precision instruments, even in the field of physics or machine building. The use of geodetic measurement methods in the field of Engineering Topographic Measurement Techniques involves, in addition to ensuring precision requirements, the choice of appropriate devices and technologies. This choice is imposed both by the previous precision calculations, starting from a maximum permissible deviation given, and by the knowledge of the execution and assembly technologies. The purpose of this paper was to study the effect and also the impact that new technologies had on the main measurement activities, and of course on measurement techniques. This review article summarizes, analyzes and discusses the current state of primary research in terms of the impact of current or developing technologies on geodetic techniques. The global corpus of primary research is growing at an unprecedented rate. It is difficult for most researchers to grasp the state of the art of a topic. A vast number of bibliographic references were taken into account, on which analyzes were performed.